Pedagogical Competencies of Islamic Religious Education Teachers in Increasing Learning Activeness Students in Middle School First Country 22 Batang Hari - Ariza Arsul; Suharni; Radhiatul Husni (International Journal of Islamic Studies Issues, 2025)
Pedagogical Competence of Islamic Religious Education Teachers in Improving Student Learning Activity at State Junior High School 22 Batang Hari, Islamic Religious Education (PAI). Nusantara Islamic Institute Batang Hari 2024. The background of what happened in this study was that there were still students who chatted with their deskmates during the learning process in class and there were still some students who did not listen to the teacher's explanation. For this reason, this study aims to determine the Pedagogy carried out by teachers in increasing student learning activity at SMPN 22 Batang Hari. To find out the obstacles faced by teachers in increasing student learning activity at SMPN 22 Batang Hari. This study uses a descriptive qualitative approach using observation, interview and documentation collection methods. The subjects in this writing are PAI teachers, principals, educators and students, while the data analysis techniques used are data collection, data reduction, data display and drawing conclusions or verification. The results of this study indicate that the teacher's pedagogical competence in increasing student learning activity has been carried out but has not been maximized. In terms of preparing lesson plans, mastering learning materials, using learning media and understanding student characters have been done well, but the use of learning media has not gone well, this is evidenced by the teacher still using the old style in explaining lessons, then there are no tools to explain related lessons. Furthermore, student learning activity has been carried out but has not been maximized, the student learning activity carried out is paying attention and listening to the teacher's explanation, asking questions to the teacher, and answering the teacher's questions, the student learning activity carried out has not been maximized, this is evidenced by there are still some students who still do not pay attention and do not listen when the teacher explains the lesson material, students do not want to ask questions related to the lesson, and cannot answer questions given by the teacher. Then the teacher's obstacle in increasing learning activity is the lack of concentration and lack of interest in learning caused by different environmental factors, this is evidenced by students who are sleepy and talk during the learning process. Efforts made by teachers in overcoming obstacles in increasing learning activity by giving appreciation/rewards to students, so that they are enthusiastic in increasing learning activity.